Impact of complete vaccination againts COVID-19 on lethality and deaths per million habitants in Asia 06/05/2022 - Mora-Alvarado, Darner A. (2023)
This study analyses the impact of complete vaccination -with two doses- on the fatality rates and deaths per million inhabitants, by COVID-19 up to 06/05/2022 in Asian. Firstly, the continent of Asia and its respective nations in the world were located. Secondly, confirmed cases, deaths and lethality due to COVID-19 were discovered. Third, the cases, deaths, lethality, deaths/million inhabitants and complete vaccination against COVID-19 were determined for each of the Asian countries. Fourth, the 10 countries with the highest death rates from COVID-19 in Asia were classified and compared with the ranking or top 10 of the nations with the highest mortality associated with COVID-19 in the world. Fifth, linear correlation calculation “r” was made between the percentages of the population with complete vaccination, with lethality and deaths/million inhabitants within the study period. The correlation between lethality and vaccination “r” was -0.54 and between vaccination and death rates per million inhabitants, “r” was 0.17. The former proves complete vaccination in Asia has been inversely proportional to lethality and deaths/million inhabitants. However, the inverse relationship is stronger with case fatality rates, defined as deaths among confirmed COVID-19 cases up to 06/05/2022.